2021
DOI: 10.14202/vetworld.2021.1564-1571
|View full text |Cite
|
Sign up to set email alerts
|

Anadara granosa shell powder improves the metabolism, testosterone level, and sound frequency of Pelung chickens

Abstract: Background and Aim: Pelung chickens make unique, pleasant, and rhythmic sounds in addition to having strong muscle mass. Performance is controlled by testosterone. A natural aromatase blocker is an agent capable of blocking the aromatase enzyme, which consequently prevents testosterone from being changed into estradiol. Such a condition results in consistently high testosterone levels. The aim of this study was to determine the effect of the administration of the shell powder of Anadara granosa on the testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Brenowitz (2013) reported that testosterone is able to increase the synthesis of brain-derived neurotrophic factor (BDNF) in HVC, then BDNF protein will be released into postsynaptic cells in the RA nucleus where it has trophic. This is also supported by the documentation of capability Anadara granosa shell to increase the singing frequency of Canaries and Pelung chickens (Astuti et al 2020;Yuneldi et al 2021d). It is then assumed that Anadara nodifera also capable of increasing the frequency and sound quality of male canaries.…”
Section: The Expression Of Cyp19 Aromatase In Syrinx Brain and Testis...mentioning
confidence: 83%
See 3 more Smart Citations
“…Brenowitz (2013) reported that testosterone is able to increase the synthesis of brain-derived neurotrophic factor (BDNF) in HVC, then BDNF protein will be released into postsynaptic cells in the RA nucleus where it has trophic. This is also supported by the documentation of capability Anadara granosa shell to increase the singing frequency of Canaries and Pelung chickens (Astuti et al 2020;Yuneldi et al 2021d). It is then assumed that Anadara nodifera also capable of increasing the frequency and sound quality of male canaries.…”
Section: The Expression Of Cyp19 Aromatase In Syrinx Brain and Testis...mentioning
confidence: 83%
“…Subsequently, 100-300 μl TMB substrate reagent was added to the wells, while the microplate was covered and incubated for 30 minutes. Then, 50 μl stop solution was added to the wells and absorbance was read using ELISA Reader or Microplate Reader (ZENIX-320) with the absorbance wave of 450 nm for 15 minutes (Yuneldi et al 2021d).…”
Section: Testosterone Level Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…[23] reported that aromatase blockers are effective in overcoming hypogonadism, as well as minimal side effects. Its use has not been highly recommended because drug preparations are not yet commercially available [24], the drug does not react long-term and the literature is still limited [25].…”
Section: The Important Role Of the Hormone Testosteronementioning
confidence: 99%